2017
DOI: 10.1093/mnras/stx2127
|View full text |Cite
|
Sign up to set email alerts
|

Parsec scale Faraday-rotation structure across the jets of nine active galactic nuclei

Abstract: A number of groups have recently been active in searching for gradients in the observed Faraday rotation measure (RM) across jets of Active Galactic Nuclei (AGNs) on various scales and estimating their reliability. Such RM structures provide direct evidence for the presence of an azimuthal magnetic field component, which may be associated with a helical jet magnetic field, as is expected based on the results of many theoretical studies. We present new parsec-scale RM maps of 4 AGNs here, and analyze their tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…It has since been confirmed by [9][10][11][12]. It has also been seen in a number of other sources (e.g., [13] and references therein). To the body of observations of 3C 273, we add those by Chen [14].…”
Section: New Vlba Images Of 3c 273 and The Variable Transverse Gradimentioning
confidence: 59%
“…It has since been confirmed by [9][10][11][12]. It has also been seen in a number of other sources (e.g., [13] and references therein). To the body of observations of 3C 273, we add those by Chen [14].…”
Section: New Vlba Images Of 3c 273 and The Variable Transverse Gradimentioning
confidence: 59%
“…This theoretical picture is supported by indirect observational evidence (AGN warm absorbers [4], Faraday RM gradients across astrophysical jets [5][6][7], polarization measurements [8], XRB Hardness-Intensity q-diagrams [9], GRB exponential afterglow decay [10], etc. ), and by state-of-the-art MHD simulations [11].…”
Section: Introductionmentioning
confidence: 78%
“…In all such cases, the inner/outer currents flow toward/away from the origin respectively. In the context of the Cosmic Battery, we are compelled to associate the observationally inferred reversed inward flowing electric current near the origin with the inner (spine) jet mentioned above [7,20].…”
Section: The Cosmic Batterymentioning
confidence: 99%
“…The first observational signature of such a transverse RM gradient was reported in the pc-scale jet of 3C 273 [174]. To date, transverse RM gradients have been reported in ∼30 pc-scale jets (see, e.g., in [165,[175][176][177][178][179][180][181][182]). Moreover, as mentioned before, the recent high resolution polarimetric studies with GMVA and RadioAstron have revealed transverse RM gradients even closer to the jet base [146,150], implying that helical B-fields in jets are preserved over a wide range of distances from the innermost regions to far beyond the VLBI core.…”
Section: Polarimetric Propertiesmentioning
confidence: 97%